Young People and the Challenges of Religious Education in the Philippines - Cornelio, Jayeel (Archīum Ateneo, 2018)
What are the challenges confronting religious education in Catholic schools? Understanding first the very context of young people is key to recognizing the gaps in religious education. The sociological input can help in making sense why for some teachers "Catholic education is failing in the Philippines." In terms of pastoral work, this question is also important in pondering how the faith can remain accessible and applicable for Filipino Catholic youth. Many might not realize that even if the Philippines is predominantly Catholic, only a very small minority have access to Catholic schools. As this chapter will spell out, religious education offered by Catholic schools in the Philippines has a more fundamental issue to confront - its relevance. In this light, the problem of religious education is not only that it is boring, in which the implicit expectation is for students to receive religious ideas as cold facts. There are far bigger social contexts confronting religious education. It has to compete for space, time, and attention with other subjects that both parents and students might see as more valuable for later success in life. At the same time, it has to confront questions about religious diversity and changing moral worldviews. If religious education were to become a beacon of hope, it needs to first comprehend the unique situation of its intended audience, the youth.